Challenges of teaching Rural Extension: practices and methodologies in the production of knowledge with family farmers - Vanilde Ferreira de Souza-Esquerdo; Shana Sampaio Sieber; Sonia Maria Pessoa Pereira Bergamasco (Universidade Federal do Norte do Tocantins, 2022)
This article aims to reflect on the challenges of teaching Rural Extension, from its methodological and practical possibilities in the context of the mandatory curriculum of the undergraduate course in Agricultural Engineering of the School of Agricultural Engineering of the State University of Campinas. We seek to understand the contribution of postgraduates who participated in the Teaching Internship Program in the expansion of the teaching practice and the role of the discipline in the training of students in dialogue with farmers. We interviewed: ten undergraduate students, three graduate students who participated in the Teaching Internship Program and three groups of family farmers who participated in the discipline. The discipline Sociology and Rural Extension in the Agricultural Engineering undergraduate course represents a counterpoint to a course with a bias oriented by and for agribusiness. This academic discipline is developed under a didactic and methodological strategy carried out with family farmers, based on the collective construction of knowledge, consolidating itself in the resistance and (re)existence of the becoming in the design of the possibilities built in the approach of the University through extension.